Symposium 5: Asynchronous learning service evaluation: A case study at TEI of Crete - Vassilakis, Kostas; Psaroudakis, Nikos; Kalogiannakis, Michail (Proceedings of the International Conference on Networked Learning, 2008)
The integration of e-learning is becoming a strategic, yet challenging goal, making it crucial for institutions of tertiary education to highlight their e-learning activities and to present a modern profile to the public. Within the networked learning environment the possibilities, accessibility and other options previously not possible in the traditional classroom now become available. In the framework of this research we are trying to analyze the use of asynchronous education platform at TEI of Crete. This platform, named "e-class", is a typical asynchronous tele-teaching platform which supports synchronous ways of communication gives to the lecturer the ability to organize his educational material and present it in various media through the network. The platform's site is http://eclass.teicrete.gr. Learning Management System (LMS) like e-class are likely to occupy an ever increasing and prominent role in the teaching and learning process, paving a new road changing the existing ways of teaching and learning, from a traditional in class way to totally synchronous or asynchronous distant one. During the last four years, TEI of Crete is using e-class to enhance traditional classroom instruction by incorporating a number of online activities. In this article, we present our experience from the use of this platform. E-class consists of a multilevel organization structure and gives to the students the opportunity to organize their study using the educational material published through the network. The platform has a pedagogical effectiveness related to the objectives of the course, offering easy and friendly navigation and use of its functions for both educators and learners. The current study is an expansion of our earlier work during the period of introducing e-class platform at TEI of Crete (2004-05). We gather information concerning the measurable usage of the major features of the platform, for the academic year 2007-08 and we try to assess them. The survey applied on courses of 10 departments of TEI of Crete. Three of these departments are concerning branches of TEI of Crete, which are located in cities of Crete away from institute's headquarters (Heraklion). The introduction of blended learning in a course may be viewed as a strategic educational development project. In 2004-05, the first period of e-class use at TEI of Crete the frequency of platform use was not encouraging, maybe, because the exploitation of the platform was fairly new. Both teachers and students regarded the platform's services as a support and complementary tool for the conventional way of education. Eventually, information for 228 electronic courses was retrieved. Not all of these electronic courses are active for the current academic year (2007-08). There is a substantial increase of platform use comparing the present state with the status during the academic year 2004-05, where 42 courses were developed (September 2005) for the same departments. Moving from traditional classroom into e-learning environment teaching and learning should adapt to the new circumstances and possibilities. In terms of pedagogy, practice and theory in networked learning is still at a relatively early stage; however, emergent trends and models point to the influence of educational theories that conceptualize learning as an active, situated and fundamentally social practice. At TEI of Crete the main use of e-class platform remains the educational content management. We argue that e-class platform could help our institution for a successful transition from a traditional to a blended way of learning and teaching. The challenge is to persuade academics at TEI of Crete that such e-learning systems could offer qualitative content and benefit for themselves, students and faculties. After almost 4 years of experience using the platform (2004-08) it will be crucial to invest in training seminars and innovative programs for the teachers of all the departments of TEI Crete.